Role of Social Media in Enhancing Agricultural Growth - Singh, Gurdeep; Singh, Pritpal; Tiwari, Devinder; Singh, Kulwant (Indian Journal of Extension Education, 2021)
A survey was conducted during 2018-19 to study the use of social media as a source of agricultural information, use patterns, preference towards different modes of information receiving and sharing, and frequency of use. The 200 rural youth were randomly selected from the South-Western Mansa district of Punjab. Results of the study revealed that only ~6 % of the young farmers were using Radio as a source of information for agriculture. The majority of the young farmers preferred social media viz. Youtube, WhatsApp, and Facebook as a source of agricultural information. The young farmers had subscribed agriculture-based channels on YouTube for agriculture-related information. Majority of young farmers had been maintaining 4-5 WhatsApp groups to share and receive information on agriculture and allied fields. Use of PAU Mobile App and Digital Newspaper (Kheti Sandesh) was also popular among farmers. Young farmers observed that use of social media has a significant impact on crop managementÂ practices. About one-fourth (~27%) of respondents had increased acreage under recommended crop varieties~16.5% had reduced the average number of sprays on rice crop, ~22.5% had been scheduling irrigation based on weather based agro-advisory and ~24.1 % were getting information on marketing of crops from social media.